Identifying the Image Attributes of Fast-food Restaurants Using Delphi Survey - Siew, Lin Yeap; Anath Rau Krishnan; Rizal Hamid (2018)
People’s hectic routines have now led to mushrooming of fast-food restaurants (FFRs), especially in urban areas. Therefore, FFR owners need to find ways to control the demand of the market. Image is one of the drivers that influences customer satisfaction, behavior intention, trust, and loyalty. FFR owners should therefore take into account all possible attributes that may affect their image, before executing any improvement strategies. Unfortunately, the image evaluation attributes proposed in past scholarly works appear to be either incomprehensive or highly redundant to each other. This study thus aims at introducing a set of attributes, which are all-inclusive yet distinctive from one another other, which could be utilised by any future studies to evaluate the image of FFRs without too much revision. The study begins by extracting an initial list of image attributes by reviewing pertinent past literature. This tentative list was then verified via a two-round Delphi survey that was participated by 10 well-experienced fast-food restaurateurs. The contribution and limitation of the study are summarised in the conclusion section.